Analisis Sentimen dan Pemodelan Topik dalam Optimalisasi Pemasaran Destinasi Pariwisata Prioritas di Indonesia - Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2021)
This article analyzes a theoretical perspective on sentiment analysis approaches and topic modeling to optimize tourism destination marketing using the Systematic Literature Review (SLR) method. The analysis consists of planning, implementation, and reporting stages. This Review Literature focuses on tourism destinations in Indonesia, in particular the ten priority destinations. The results of this study are that the sentiment analysis approach and topic modeling can optimize the marketing strategy of ten priority destinations in Indonesia. Nevertheless, the sentiment analysis results need to be explicitly described based on tourist attraction, tourism supporting accommodation, tourism support accessibility, and tourist activities. Furthermore, modeling topics about tourism destinations need to be classified in-depth based on tourism support, accessibility of tourism support, tourist activities, tourist attractions, and the context of vulnerability.